The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12987-020-00217-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes is associated with familial idiopathic normal pressure hydrocephalus: a case–control comparison with family members

Abstract: Background The pathophysiological basis of idiopathic normal pressure hydrocephalus (iNPH) is still unclear. Previous studies have shown a familial aggregation and a potential heritability when it comes to iNPH. Our aim was to conduct a novel case-controlled comparison between familial iNPH (fNPH) patients and their elderly relatives, involving multiple different families. Methods Questionnaires and phone interviews were used for collecting the data and categorising the iNPH patients into the familial (fNPH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…Patients with iNPH have a higher comorbidity rate of diabetes, which is more than double, compared with an age-adjusted general population [ 64 66 ]; however, the causal relationship between diabetes and iNPH has not yet been determined. Studies from patients with vestibular schwannoma have reported to have higher occurrence of communicating-type hydrocephalus, rather than non-communicating hydrocephalus due to the fourth ventricular compression [ 67 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with iNPH have a higher comorbidity rate of diabetes, which is more than double, compared with an age-adjusted general population [ 64 66 ]; however, the causal relationship between diabetes and iNPH has not yet been determined. Studies from patients with vestibular schwannoma have reported to have higher occurrence of communicating-type hydrocephalus, rather than non-communicating hydrocephalus due to the fourth ventricular compression [ 67 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was associated with decreased gBOLD-CSF coupling and a faster gBOLD-CSF coupling decline rate. Indeed, previous studies found that diabetes was associated with both hydrocephalus ( Räsänen et al, 2020 ) and SVD progression ( Bernbaum et al, 2015 ). Our results further support their associations.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption demonstrated a correlation with iNPH development possibly due to ethanol-induced decrease in beating frequency of motile cilia and consequent dysfunction on the ependymal cells of ventricles ( Omran et al, 2017 ; Ghaffari-Rafi et al, 2020 ). Although iNPH patients present with increased morbidity of diabetes, the causal relationship has not been concluded ( Hudson et al, 2019 ; Rasanen et al, 2020 ). The speculative pathogenesis may be attributed to high concentration of sugar and increased fluid viscosity in CSF.…”
Section: Human Genetic Studies Of Hydrocephalusmentioning
confidence: 99%